Refleksi Filsafat tentang Reformasi Pendidikan - Ahmad Samawi (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 1999)
The total reformation which has been underway in Indonesia has touched politics, economy, law, but education, which is the essential matter in human life. Prior to education reformation, there should be a philosophical reflection which discusses the life principles of Indonesian people. This means that reformation as the change of Indonesians’ behaviors should be based on the basic nature of Indonesians as human beings with dignity. Education reformation is urgently required since life changes very fast, particularly in science, technology, and information. Reformation must consider the basic values and Proclamation ideals which have been established by the founding fathers.